Bioactive Lipoxygenase Metabolites Stimulation of NADPH Oxidases and Reactive Oxygen Species - Cho, Kyung-Jin (Korean Society for Molecular and Cellular Biology, 2011)
In mammalian cells, reactive oxygen species (ROS) are produced via a variety of cellular oxidative processes, including the activity of NADPH oxidases (NOX), the activity of xanthine oxidases, the metabolism of arachidonic acid (AA) by lipoxygenases (LOX) and cyclooxygenases (COX), and the mitochondrial respiratory chain. Although NOX-generated ROS are the best characterized examples of ROS in mammalian cells, ROS are also generated by the oxidative metabolism (e.g., via LOX and COX) of AA that is released from the membrane phospholipids via the activity of cytosolic phospholipase A(2) (cPLA(2)). Recently, growing evidence suggests that LOX- and COX-generated AA metabolites can induce ROS generation by stimulating NOX and that a potential signaling connection exits between the LOX/COX metabolites and NOX. In this review, we discuss the results of recent studies that report the generation of ROS by LOX metabolites, especially 5-LOX metabolites, via NOX stimulation. In particular, we have focused on the contribution of leukotriene B(4) (LTB(4)), a potent bioactive eicosanoid that is derived from 5-LOX, and its receptors, BLT1 and BLT2, to NOX stimulation through a signaling mechanism that leads to ROS generation.